The implications of COVID‐19 for health workforce planning and policy: the case of Peru. (19th February 2021) - Rees, Gareth H; Peralta Quispe, Felipe; Scotter, Cris
Abstract: Like many countries Peru is confronting uncertainties due to the COVID‐19 pandemic and its consequences. This is having impacts not only on health systems but also on the planning and preparation of its workforces. In this case article we summarise the progress Peru has been making to improve its workforce capacity and planning and review how Peru has coped with the stresses put on its health system arising from the pandemic. By recounting the responses that the Ministry of Health made through mobilising existing capabilities, additional workers and collaboration with health science faculties and health professional colleges, the article identifies that a longer‐term planning perspective based on skills that services require is something that Peru may consider to compliment the health workforce investments that are already being made. As such, this case provides an example for workforce planners and policy makers to contemplate when considering health workforce planning in post‐COVID uncertainty.